“Antiques”: forgery of ancient icons in Russia in the 19th and early 20th centuries - Walczak Dorota (Studia Humanitatis, 2023)
This article describes such an unprecedented phenomenon of Russian icon painting in the 19th and early 20th centuries like mass forgery of ancient icons with the aim of their subsequent sale to believers or collectors. This craft has been developing in different villages of the Vladimir province since the 18th century and initially implies the presence of a well-established system of old-style icon painters (“starinshchiki”) and wandering icon dealers (“ofenees”). The author reveals the underlying causes of this phenomenon, describes the main ways of forging ancient icons and analyses the artistic means that were used by icon painters to stylize “antique”. A connection is established between the Old Believer type of piety and the fashion for antiquity and the increase in demand for “ancient” icons, and thereby the development of the craft of “starinshchiki”.